Direct parallel Poisson solver with the multiply grid spacing support for plasma simulation via PIC method - Dadyka, D.I.; Anisimov, I.O. (Вопросы атомной науки и техники, 2016)
Problem of the plasma simulation area decomposition for Poisson equation solution via PIC method using parallel computing is treated. Modification of the existing method moving to reduction of the computational complexity is discussed. The approach to use different grid spacing for subdomains is proposed. Method of approximate solution that results in the substantial decrease of the data transmitted is brought forward